Design and performance test of overshot water wheel with variation of inner diameter - Alif Ramadhan; Asral (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
This research was conducted to find out how to design an overshot type waterwheel and the effect of variations inner diameter of the overshot type waterwheel on work performance, the waterwheel is classified into the category of picohydro power plants that can generate electricity less than 5000 Watt, the overshot type waterwheel has a motion mechanism using a push water that comes from the top of the waterwheel, the overshot type waterwheel has greater efficiency than other types of waterwheels, therefore to get a large amount of power an overshot type waterwheel is used. The testing of the designed waterwheel has been adapted to conditions in the Riau Province area, where the Riau area has many rivers and reservoirs so it is suitable for use for hydroelectric power plants, and the height of the water fall in the Riau area on average is about 1 meter to 3 meters. The size of the inner diameter of the waterwheel was tested starting from the size of 0.25 m, 0.5 m, 0.75 m, this size variation was made to test whether the effect of the inner diameter of the waterwheel affects the amount of torque produced by the waterwheel by using the same discharge so that it can produce power optimally, a waterwheel with an inner diameter of 0.5 m has the best performance because the efficiency of the waterwheel is the highest, from this test it can be seen that the dimensions of the waterwheel must be directly proportional to the discharge given to the waterwheel so that the power generated more optimal.